2019
DOI: 10.1111/tpj.14292
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive mass spectrometry‐guided phenotyping of plant specialized metabolites reveals metabolic diversity in the cosmopolitan plant family Rhamnaceae

Abstract: Plants produce a myriad of specialized metabolites to overcome their sessile habit and combat biotic as well as abiotic stresses. Evolution has shaped the diversity of specialized metabolites, which then drives many other aspects of plant biodiversity. However, until recently, large-scale studies investigating the diversity of specialized metabolites in an evolutionary context have been limited by the impossibility of identifying chemical structures of hundreds to thousands of compounds in a time-feasible mann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 45 publications
0
52
0
1
Order By: Relevance
“…Another case where we demonstrate the efficiency of MolNetEnhancer for enhancing the chemical annotation of metabolomics data is our previous study on the plant family Rhamnaceae [25]. Rhamnaceae is a cosmopolitan family including about 900 species, and Rhamnaceae species are known for their exceptional morphological and genetic diversity, which are thought to be caused by the wide geographic distribution and different habitats [40].…”
Section: Case Study 2: Annotation Of Rhamnaceae Specialized Metabolitesmentioning
confidence: 66%
See 3 more Smart Citations
“…Another case where we demonstrate the efficiency of MolNetEnhancer for enhancing the chemical annotation of metabolomics data is our previous study on the plant family Rhamnaceae [25]. Rhamnaceae is a cosmopolitan family including about 900 species, and Rhamnaceae species are known for their exceptional morphological and genetic diversity, which are thought to be caused by the wide geographic distribution and different habitats [40].…”
Section: Case Study 2: Annotation Of Rhamnaceae Specialized Metabolitesmentioning
confidence: 66%
“…After combining this chemical class annotations with taxonomic information of each molecular feature, the normalized distribution pattern of different classes of metabolites were analyzed. This revealed that the taxonomic clade Rhamnoid exhibits more diversified flavonoids, carbohydrate, and anthraquinones, while the Ziziphoid clade produces various triterpenoids and triterpenoid glycosides [25].…”
Section: Case Study 2: Annotation Of Rhamnaceae Specialized Metabolitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular networking [31] uses spectral similarities to group metabolites into Molecular Families (MF). These MFs potentially correspond to chemical classes and have proven invaluable in enhancing the putative identifications of unknown metabolites [9,14]. In MS2LDA, metabolites are grouped by co-occurring fragments and neutral losses into Mass2Motifs that reveal potential chemical substructures [28].…”
Section: Introductionmentioning
confidence: 99%